Macbeth - Shakespeare, William, 1564-1616.; Crowther, John (John C.) (New York, NY : Spark Pub., 2003)
Presents the original text of Shakespeare's play side by side with a modern version, with marginal notes and explanations and full descriptions of each character.
Keywords: Macbeth, -- King of Scotland, -- 11th cent. -- Drama; Shakespeare, William, -- 1564-1616.; Regicides -- Drama; Young adult drama, English; Plays; English literature -- History and criticism; Scotland -- Drama